A review of ecosystem service supply in tropical marine ecosystems and its relationship to habitats in the Great Barrier Reef - Mark A. Ford-Learner; Jane Addison; Graeme S. Cumming (Ecosystems and People)
The benefits that people obtain from marine and coastal ecosystems are numerous and complex. Although marine ecosystem service approaches are increasing in prominence, relatively little is known about how marine ecosystem service provision relates to individual habitat types at the level at which they are typically considered in management and policy. To clarify and operationalise the links between tropical marine habitat types and ecosystem services, we undertook a literature review and a spatial mapping exercise. First, we systematically reviewed published studies of tropical marine ecosystem services, with the aim of describing the strengths and weaknesses of existing knowledge and directly linking identified ecosystem services to specific marine habitat types. Second, we tested whether we could use our new synthesis to connect ecosystem services to habitat types by mapping ecosystem service supply in a well-studied and iconic marine protected area, Australia’s Great Barrier Reef Marine Park. The review showed that while some habitat types (particularly mangroves, seagrass and coral reefs) and their associated ecosystem services are well described, others (e.g. beaches, mudflats and surface waters) are far less explored. The mapping exercise showed that habitat mapping can provide a potentially useful interface between the types and locations of marine ecosystem services. Overall, tropical marine ecosystem services in our study area appear to be primarily clustered around coastlines and reefs and in close proximity to human populations. Our results highlight the potential value of ecosystem services approaches for informing management decisions that better connect ecological and human values in tropical marine environments.